(2a-3)+(3a-1)=

Simple and best practice solution for (2a-3)+(3a-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2a-3)+(3a-1)= equation:


Simplifying
(2a + -3) + (3a + -1) = 0

Reorder the terms:
(-3 + 2a) + (3a + -1) = 0

Remove parenthesis around (-3 + 2a)
-3 + 2a + (3a + -1) = 0

Reorder the terms:
-3 + 2a + (-1 + 3a) = 0

Remove parenthesis around (-1 + 3a)
-3 + 2a + -1 + 3a = 0

Reorder the terms:
-3 + -1 + 2a + 3a = 0

Combine like terms: -3 + -1 = -4
-4 + 2a + 3a = 0

Combine like terms: 2a + 3a = 5a
-4 + 5a = 0

Solving
-4 + 5a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 5a = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 5a = 0 + 4
5a = 0 + 4

Combine like terms: 0 + 4 = 4
5a = 4

Divide each side by '5'.
a = 0.8

Simplifying
a = 0.8

See similar equations:

| 20-5y/2=x | | (3x+5y)dx+(4x+6y)dy=0 | | 1/2y^2-5/2y-12 | | 5(5x-3)+11=-3 | | 15w^2-1w-2=0 | | 0.5(x+100)+1.3x=131 | | (-7/3u-9)-4=(-8/u-3) | | x^2/10+x+2/3=0 | | 0.6x+8.1=7.2 | | 5x-3-4x-10=27 | | 2+2x/7+5-x/5+48/35 | | 3x^9-15x^8=9x^7 | | X^2-12X-676=0 | | 5(5x-3)+11=3 | | -2[5(x-2)-10]=80 | | 0.25x^2-1/2x=1 | | 2x+3-5=-3 | | 18-(3x+5)=8 | | 10(a-1)-2(a+2)+3=13 | | 9(4-y)+2=-2(y-4)-3 | | 8x-1+4=6 | | .16(y-1)+.06y=.18y-.3 | | 7-6x/4 | | 7-4/x | | 5x-y=100 | | .75x+.05(20-x)=.10(-46) | | x^2+16=64 | | 4p+7=12+3p | | 7.6x+3=6.6x | | r=51-2r | | (4x+5)(3y-7)= | | 6(4-3)-5(4+2)=8 |

Equations solver categories